2009
DOI: 10.3747/pdi.2009.00132
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Patency and Peritoneal Morphology and Function in a Rat Model of Citrate-Buffered Peritoneal Dialysis

Abstract: A positive acute effect of citrate on UF was confirmed and conserved over time. Citrate PD strongly improved PD catheter patency time compared with lactate. Both citrate PD and lactate PD induced negative long-term effects on UF compared with control animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Citrate has been proposed as an alternate buffer for lactate or bicarbonate for good theoretical reasons, including anticoagulant properties and antioxidant properties. In this issue of Peritoneal Dialysis International , Cavallini and Braide (7) extend their observations on the effect of adding citrate (10 mmol/L) to lower lactate concentrations from 40 to 30 mmol/L in single daily dialysis dwells in rats. Previously, they reported that a single dwell of citrate-supplemented dialysate improved UF in rats and humans (8,9).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Citrate has been proposed as an alternate buffer for lactate or bicarbonate for good theoretical reasons, including anticoagulant properties and antioxidant properties. In this issue of Peritoneal Dialysis International , Cavallini and Braide (7) extend their observations on the effect of adding citrate (10 mmol/L) to lower lactate concentrations from 40 to 30 mmol/L in single daily dialysis dwells in rats. Previously, they reported that a single dwell of citrate-supplemented dialysate improved UF in rats and humans (8,9).…”
mentioning
confidence: 93%
“…This may be a statistical effect of small numbers as there appears to be a disproportionately high osmotic UF in the initial citrate exposure group that then creates the larger difference in net UF. However, the authors state there was no significant difference in UF when the difference in UF (initial study vs final study) for each animal was considered (7). Thus, the findings probably reflect the problem of relatively small numbers of animals in each group.…”
mentioning
confidence: 99%
See 1 more Smart Citation